The influence of friction stir welding of dissimilar AZ31 and AZ91 magnesium alloys on the microstructure and tensile properties - N. S., Mohamed; Juliawati, Alias (Universiti Malaysia Pahang, 2019)
Joining of magnesium alloys was successfully performed by friction stir welding (FSW) technique. This study was aimed in characterizing the microstructure developed after the FSW and its influence on the mechanical properties. The developed microstructure was observed by using optical microscopy, from the cross-sectional side of welded sample. In this study, FSWed of two dissimilar magnesium (Mg) alloy sheets with low aluminum (AZ31) and high aluminum (AZ91) content were successfully conducted at varied welding speed of 60, 80 and 100 mm/min and tools rotational rate of 800, 1000 and 1200 rpm. The microstructure consists of fine and equiaxed recrystallized grain structure especially at the stir zones. The result of the tensile test indicated that the grain size variation of the joint showed an effect on the mechanical properties and fracture location of the joint. An increasing trend of hardness profile revealed more amount of dissolution of aluminum at the stir zone. From the result, FSW can be concluded as effective joining technique for dissimilar magnesium alloys and produced a defect free joint.